Pilot’s attention distributions between chasing a moving target and a stationary target - Li, Wen-Chin; Yu, Chung-San; Braithwaite, Graham; Greaves, Matthew J. (Aerospace Medical Association, 2016)
Introduction: Attention plays a central role in cognitive processing; ineffective attention may induce accidents in flight operations. The objective of current research was to examine military pilots’ attention distributions between chasing a moving target and a stationary target. Method: Thirty-seven mission-ready F-16 pilots participated in the current research. Subjects’ eye movements were collected by a portable head-mounted eye-tracker during tactical training in a flight simulator. The scenarios of chasing a moving target (air-to-air) and a stationary target (air-to-surface) consist of three operational phases; searching, aiming and lock-on to the targets. Results: The findings demonstrated significant differences in pilots’ percentage of fixation during searching phase between air-to-air (M=37.57, SD=5.72) and air-to-surface (M=33.54, SD=4.68). Fixation duration can indicate pilots’ sustained attention to the trajectory of a dynamic target during dog-fight manoeuvers. Aiming for the stationary target with larger pupil size (M=27105 pixel2, SD=6565 pixel2) reflects higher cognitive loading than aiming to the dynamic target (M=23864 pixel2, SD=8762 pixel2). Discussion: Pilots’ visual behavior is not only closely related to attention distribution, but also significantly associated with task characteristics. Military pilots demonstrated various visual scan patterns for searching and aiming to different types of targets based on the research settings of flight simulator. The findings would facilitate system designers’ understandings of military pilots’ cognitive processes during tactical operations. It will assist human-centered interface design to improve pilots’ situational awareness. The application of an eye-tracking device integrated with a flight simulator is a feasible and cost-effective intervention to improve efficiency and safety of tactical training.
Keywords: attentional processes; eye movements; mental workload; simulation and training; situation awareness